Promoting the use of bioenergy in developing nations: a CDM route to sustainable development - Dirisu, Joseph O.; Salawu, Enesi Y.; Ekpe, Ikenna C.; Udoye, Nduka E.; Falodun, Oluwasegun E.; Oyedepo, Sunday O.; Ajayi, Oluseyi O.; Kale, Sandip A. (Frontiers in Energy Research, 2024)
The study focused on a forensic assessment of bioenergy utilization in developing countries, emphasizing how to improve bioenergy resources for a sustainable economy and development. First, a holistic review of energy sources and their impacts on sustainable development was highlighted. The study also looked at the relationships between various energy sources, both the supply and demand of energy, as the population statistics in developing countries. However, renewable energy is yet to be harnessed fully as it lagged by 0.7%. Shockingly, the African continent is backward in both the global energy supply and in tapping renewable energy sources, as only 6 % is contributed. More so, applying a clean development mechanism (CDM) for energy utilization and control shows that net emission reduction and global temperature reduction of 1.5 o C by 2030 is attainable. Thus, helping to realize low-cost and sustainable energy (SDG 7) and sustainable cities and communities (SDG11). Further, the assessment of the level of bioenergy availability and its utilization shows that 10% of the world's energy is provided by bioenergy. Interestingly, it is available in every region in the form of biomass. The study is helpful for stakeholders, policymakers, and governments managing the affairs of the energy sector on the need to formulate policy that will guide effective bioenergy utilization and reduction in greenhouse gas emissions, especially in developing countries thereby, promoting sustainable economic growth.